GR_GERICHTE SKA 2003 20 vom 19. August 2003 , Lohnpfändung (Lohnzession/Verfahren) - GR Gerichte (2003)
Pfändung/Verlustschein (Berechnung Notbedarf, Pfändung 13. Monatslohn) | Beschwerde 17 Abs. 1 SchKG